Complement Component C1q as Serum Biomarker to Detect Active Tuberculosis - Lubbers, Rosalie; Sutherland, Jayne S.; Goletti, Delia; de Paus, Roelof A.; van Moorsel, Coline H. M.; Veltkamp, Marcel; Vestjens, Stefan M. T.; Bos, Willem J. W.; Petrone, Linda; Del Nonno, Franca; Bajema, Ingeborg M.; Dijkman, Karin; et al. (Frontiers in Immunology, 2018)
Background: Tuberculosis (TB) remains a major threat to global health. Currently, diagnosis of active TB is hampered by the lack of specific biomarkers that discriminate active TB disease from other (lung) diseases or latent TB infection (LTBI). Integrated human gene expression results have shown that genes encoding complement components, in particular different C1q chains, were expressed at higher levels in active TB compared to LTBI. Methods: C1q protein levels were determined using ELISA in sera from patients, from geographically distinct populations, with active TB, LTBI as well as disease controls. Results: Serum levels of C1q were increased in active TB compared to LTBI in four independent cohorts with an AUC of 0.77 [0.70 ; 0.83]. After six months of TB treatment, levels of C1q had normalized to those of endemic controls, indicating an association with disease rather than individual genetic predisposition. Importantly, C1q levels in sera of TB patients were significantly higher as compared to patients with sarcoidosis or pneumonia, clinically important differential diagnoses. Moreover, exposure to other mycobacteria such as M. leprae (leprosy patients) or BCG (vaccinees) did not present with elevated levels of serum C1q. In agreement with the human data, in non-human primates challenged with Mycobacterium tuberculosis, increased serum C1q levels were detected in animals that developed progressive disease. Conclusions: We propose that the addition of C1q to current biomarker panels may provide added value in the diagnosis of active TB.